THE THEORY OF SPACE CONCEPTS RELATED TO FORMULA GREEN OPEN SPACE - Aldrin Yusuf Firmansyah (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2014)
The concept of green open space is still stuck on the concept of space-based theory of absolute space by Issac Newton, who see space as a separation between the mass of the building as a container (solid) and open space (void). Meanwhile, the demands of the world's cities today to combine city life with the natural environment in the city increasingly limited land has resulted in the embodiment of innovation of green open spaces, combined with the mass of the building, either vertically, horizontally, multilevel, and a roof garden. Therefore, the thought about the concept of green area calculation shifts related to the building envelope as an instrument to control the development of the building as a 3-dimensional, in the form of an imaginary space by the slope of the field open sky (Sky Exposure Plane / SEP) were measured from a specific point on the surface of the surrounding road. This paper aims to formulate the calculation of green coverage in relation to the SEP. The concept of SEP operationally still only concerned with building setback. This research method is descriptive qualitative in 2 stages. The first step is the influence of the theory of space to green space on the site and the building. The analysis is supported by the classification of urban space. The second step is the calculation formula of green coverage in relation to the SEP by Surabaya city government regulation no. 7, March 23, 1992, so the calculation formulation contextual conditions in Indonesia. The results showed that the formulation of green coverage in relation to the SEP is an instrument to determine the limit on the development of 3 dimensional green space.